ICT Tools of Professional Teacher Activity: A Comparative Analysis of Russian and European Experience - Tatiana N.; Tatiana B.; Olga V. (National Research Mordova State University, 2018)
Introduction: electronic, distance and blended educational technologies are actively used in modern teaching and learning process. The relevance of the study is predetermined by the necessity to consolidate teachers' competencies in the field of ICT tools. The purpose of the article is to study and compare the competences of Russian and European teachers in using pedagogical ICT tools. Materials and Methods: comparison and analysis of domestic and foreign pedagogical practices are used. Data was obtained with the help of elaborated questionnaires for teachers with sufficient experience in the use of ICT. Results: the results of a comparative analysis of data characterising the experience of pedagogical ICT tools application by teachers of Russian and foreign universities are presented. Similar trends and problem areas were identified. They relate both to the use of information technology and electronic educational resources and to the variability of the educational opportunities. The obtained results show that the educational request of students in the electronic environment is not always sufficiently recognised and taken into account by teachers. The revealed general directions of research in the area of ICT tools application in teaching activity indicate the tendencies of the integration of the Russian and European experience into the global information and educational space. Discussion and Conclusions: in summary, Russian and foreign teachers have similar competencies in the use of educational ICT tools. They apply the tools to the learning process with varying intensity depending on the experience of distance educational services implementation, the policy of an educational institution, and the awareness of the blended learning specifics. The practical significance of the results it the following: firstly, the directions that need to be strengthened in vocational training programs for future and practicing teachers are identified; secondly, the range of possible reasons for the difficulty of Russian universities integrating into the global information and educational space are assumed. More broadly, further research is needed to determine the structure of the competences of the use of pedagogical ICT tools. The findings of this study have a number of important implications for futur e educational practice.